Throughput optimization of rayleigh channel using various parameters - Arefin, Md. Taslim; Shameem, Mushfeq-us-Shameem; Awal, A.L.M Ashfaqul (BRAC University, 2010)
In wireless communication throughput is a key factor to measure the quality of wireless data link. Throughput is defined as the number of information bits received without error per second and we would naturally like this quantity as to be high as possible. This research work looks at the problem of optimizing throughput for a packet based wireless data transmission scheme from a general point of view. The purpose of this work is to show the very nature of throughput and how it can be maximized that means how we can optimize the throughput by observing its certain changing parameter such as transmission rate, packet length, signal-to-noise ratio (SNR) etc. Our main result is a mathematical technique for determining the optimum transmission rate and packet size as a function of the other variables. The key to maximizing the throughput rate is maintaining the signal-to-noise ratio at an optimum level determined by the nature of the channel. Have We tried to take a more a more general look at throughput by considering its definition for a packet-based scheme and how it can be maximized based on the channel model being used. In this research work we have used Rayleigh Fading Channel.